The Effect of Various Additive Materials on Physical Quality and Silase Chemical Rice Chemistry (Zea mays.L) - Marselinus Banu; Hery Supratman; Yuli Astuti Hidayati (Fakultas Peternakan, Universitas Padjadjaran, 2019)
Purpose of this study was to determine the extent from the influence of various additives on the physical and chemical quality of silage of corn straw (Zea mays. L). This study was carried out using the experimental method and Completely Randomized Design (CRD) with 4 treatments consisting of P0: corn straw silage without additives, P1: corn straw silage + 0.5% Heryaki powder, P2: corn straw silage + 5% cassava flour and P3: corn straw silage + 5% sago flour and 5 replications. Data on physical quality (odor, color and texture) were analyzed descriptively while chemical quality data (pH and ammonia were analyzed using ANOVA variance, followed by Duncan's Multiple Distance Test. Giving additives of Heryaki powder, cassava flour and sago flour showed good results on the physical quality of corn straw silage (sour smell, brownish green and texture does not clot) and has a significant effect on honey and ammonia.